Development of basic reading skills in Latin: a corpus-based tool for computer-assisted fluency training - Milena Kuehnast; Konstantin Schulz; Anke Lüdeling (Cogent Education)
The present paper evaluates the processes of reading acquisition in Latin from the component-skills approach and discusses how advances in reading in modern foreign languages could be adapted to the specific needs of Latin as a historical language. Compared to the holistic and socially embedded approaches to modern foreign language acquisition, the grammar-translation method traditionally used in schools shows considerable weaknesses in the development of basic reading skills in Latin. Therefore, we address the possible advantages of corpus-based teaching strategies and present Machina Callida, a psycholinguistically informed e-tutor suitable for supporting Latin vocabulary acquisition and reading comprehension at beginner and intermediate levels. Using digital corpora of original Latin texts, the application semi-automatically generates contextualized vocabulary exercises tailored to the needs of different groups of learners. Through its integration with the research data repository Zenodo, Machina Callida supports online collaboration in the creation and distribution of open educational resources through crowdsourcing.